Rebel alliances: the means and ends of contemporary British anarchisms - Franks, Benjamin (2000)
This thesis examines, classifies and evaluates the tactics and organisational methods of British and Irish anarchist groups, which operated in the period 1984-1999 (although reference is made to groupings and events outside of this period). The thesis explains how class struggle anarchism, which was a minority trend even within the libertarian milieu, has developed into a significant and lively (anti-)political movement. This thesis examines recent groups through their own publications and their accounts of their recent actions.